Estudo dos efeitos do tratamento com antimônio associado à pentoxifilina na modulação da resposta imunológica in situ de pacientes com leishmaniose mucosa - Luiza Cenizio Barbieri (2012)
Human infection with Leishmania braziliensis can lead to cutaneous leishmaniasis (CL) or mucosal leishmaniasis (ML). ML is associated with exacerbation of inflammatory immune response, causing extensive damage tissue. Treatment of leishmaniasis is still based on the use of pentavalent antimony (SbV). However, the failure of this treatment is common and resistant parasites have been detected. Due to the problems resulting from SbV treatment a wide variety of alternative therapies has been evaluated for leishmaniasis treatment. The aim this study was to investigate the effect of antimony associated or not to pentoxifylline (Ptx) in the modulation of the in situ immune response of ML patients. We evaluated the frequency of T CD4+, CD8+ cells and CD68+ macrophages, as well as the expression of cytokines IFN-, TNF- and IL-10+ and cytotoxic molecules granzyme A+ and the correlation between these immunological parameters in lesions from ML patients before and after SbV and SbV associated with Ptx treatment, by confocal microscopy. We did not observe differences in the numbers of the different cell populations or cytokines and granzyme A, comparing lesions from patients before and after treatment with SbV. Lesions from ML patients after Ptx associated with SbV treatment had lower frequency of macrophages, as compared to lesions before treatment. There was no change in expression of IFN-, IL-10 and granzyme A in lesions from patients after SbV + Ptx treatment. However, Ptx associated with SbV treatment leads to a reduction in the number of CD68+TNF-+ cells. There were no differences in the frequencies of cell populations and cytokines comparing between lesions from patients submitted to the different treatments. The Ptx associated with SbV treatment induced loss of positive correlation between the inflammatory infiltrate and the number of TNF-+ cells, as well as the number of CD8+ T cells and granzyme A+ cells. Ptx associated with SbV treatment may result in a modulation of the immune response more efficient and consequently an accelerated healing